2022
DOI: 10.21931/rb/2022.07.03.29
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of lipid profile with HbA1c in type 2 diabetic Iraqi patients

Abstract: Insulin-induced hyperglycemia is the hallmark of diabetes mellitus (DM), including various metabolic disorders. Diabetic people are more likely to develop dyslipidemia, hypertension, and obesity. Type 2 diabetes ‎(T2DM), the most common illness, is generally asymptomatic in its early stages and can go misdiagnosed for years. Diabetes screening may be beneficial in some cases since early identification and treatment can lessen the burden of diabetes and its consequences.‎ This study aimed to find the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Regarding sex, the majority of both groups were males. Our results are supported by the study of Nesheli et al 6,7 as they reported that the mean age of cases with inhibitors was 10.22 years. Their results revealed that the production of inhibitors in young populations was more significant than in older ones.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Regarding sex, the majority of both groups were males. Our results are supported by the study of Nesheli et al 6,7 as they reported that the mean age of cases with inhibitors was 10.22 years. Their results revealed that the production of inhibitors in young populations was more significant than in older ones.…”
Section: Discussionsupporting
confidence: 91%
“…Also, A allele distribution was increased in positive inhibitors at 11.1%, then in negative inhibitors at 2.8%. Table (6) Following logistic regression analysis and adjusting for confounding factors, the only independent predictor of positive inhibitors was the number of factors 8 exposure days > 20 days (OR = 3.8) with a 95% CI (1.05-13.7).Table (7).…”
Section: Resultsmentioning
confidence: 99%
“…The lifetime risk of getting a diabetic foot ulcer has been estimated to be as high as25%, and the reported annual incidence of diabetic foot ulceration ranges from 2.1% to 7.4% (10). It has been estimated that up to 15% of persons with T2DM have DFUs [11]. Globally, the incidence is estimated to be 6.3% (95%) with a reported 13.0% prevalence in North America.…”
Section: Epidemiology Of Diabetic Footmentioning
confidence: 99%